(untitled) (Research, Society and Development, 2021)
Among advanced effluent treatment technologies, membrane separation processes stand out for their wide range of applications, which water desalination, industry process, and water treatment. The nanoparticles used as additives in the membrane formation can bring improvements to the performance and effectiveness of membrane filtration, thus forming nanocomposite membranes, which, depending on their matrix, may have desirable and undesirable characteristics. In most cases, polyamide membranes have been widely studied and used as well in their pure form as with the addition of one or more additives, which can confer important improvements, such as reducing roughness, increasing porosity, correcting defects, improving permeability, among others. Titanium dioxide (TiO2) is one of the additives that has achieved prominence as an option to increase porosity, permeability, hydrophilicity, and reduce the effect of fouling. As such, it is applied in several experimental studies that describe their behavior when it is incorporated into membranes. This study aims to review the main cases involving TiO2 used as an additive in polymeric membranes and to present the effects caused by, according to the methods and techniques used in recent literature.